Nest Architecture and Animals Associated with Neoponera verenae (Forel) (Formicidae, Ponerinae) - Moleiro, Hugo R [UNESP]; Silva-Melo, Adolfo Da [UNESP]; Giannotti, Edilberto [UNESP] (Universidade Estadual de Feira de Santana, 2021)
The nests of ants Neoponera have chambers that can also be occupied by other species of organisms that can be tenants, visitors or prey. However, few studies have considered the assemblage of the associated species and described their composition. This study aimed to describe the architecture and catalog the visitors and prey species found in Neoponera verenae nests. Talcum powder was pumped inside eight nests to mark the chambers and tunnels. The nests were then excavated to describe the architecture and obtain measurements of chambers. The associated species encountered in the nests were collected and identified allowing us to obtain new records of visiting (Linepithema sp., cryptodesmid millipedes and Neotropacarus sp.) and prey taxa (membracids, apid bees and springtails) of N. verenae. Generally, nests had a single entrance hole and a depth of up to 42 cm. Nest chambers were found with three basic forms, elliptical, hangers and boot. Although studies show that this species can occupy abandoned nests of leaf-cutting ants, we found that the nests of N. verenae were more similar to those of Ectatomma ants. Indeed, we found one of the N. verenae nests was attached to a Ectatomma edentatum nest, leading us to suggest that N. verenae may occupy abandoned nests or displace other ants to occupy them.
Keywords: Ants; Hypogeic invertebrates; Nest construction; Predation